1977
DOI: 10.1002/1097-0142(197711)40:5<2343::aid-cncr2820400551>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblastic contraction in spontaneous regression of multiple congenital mesenchymal hamartomas

Abstract: Subcutaneous nodules from a newborn boy with "multiple fibromatosis" involving the head, neck, trunk, and all four extremities were studied by light microscopy, transmission electron microscopy, and immunofluorescent techniques. Light microscopy suggested a hamartomatous process with fibroblastic adipose, vasoformative and apparent smooth muscle components. The principal cell population combined ultrastructural characteristics of both fibroblasts and smooth muscle cells. Immunofluorescent studies revealed bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(25 citation statements)
references
References 16 publications
3
22
0
Order By: Relevance
“…It seems likely that tumour encapsulation may be at least partially responsible for tumour dormancy and slow regression, because every dormant and regressing MC2 implant examined histologically was enclosed in a cellular-fibrous capsule. A connection between tumour fibrosis and tumour regression has also been noted by Benjamin et al (1977) and by Key and Haskill (1981).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…It seems likely that tumour encapsulation may be at least partially responsible for tumour dormancy and slow regression, because every dormant and regressing MC2 implant examined histologically was enclosed in a cellular-fibrous capsule. A connection between tumour fibrosis and tumour regression has also been noted by Benjamin et al (1977) and by Key and Haskill (1981).…”
mentioning
confidence: 73%
“…By the location of resorcin-crystal violet, injected via the left ventricle, it was found that such tumours were also invariably without active vascular supply, even when the surrounding stroma was highly vascular. The apparent effect of the encapsulation was to occlude the vascular supply to the tumour, possibly by the suggested mechanism of collagen fibre shrinkage (Benjamin et al, 1977). Progressively growing tumours, expanding into the surrounding stroma, were well vascularised.…”
Section: Resultsmentioning
confidence: 99%
“…Electron microscopic examination reveals features of both fibroblast and smoothmuscle cells. 6 The solitary lesions have a low rate of recurrence after surgical excision. In the multiple type, the prognosis depends on the extension of visceral involvement and the eventual spontaneous regres¬ sion of the lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The fibrous tissue formation often associated with mammary carcinomas suggests that collagen formation is a defense mechanism which, when successful, contains a primary tumor in a capsule, The fibrous encapsulation can inhibit the release of potentially metastatic tumor cells and can, by collagen fiber shrinkage (21), lead to a tumor's dormancy or destruction by constriction and occlusion of its vascular supply (22,23). The mammary carcinoma MC2 may be rejected by about 20% of syngeneic, unimmunized, untreated female implant recipients after a period of subcutaneous (s.c.) growth to as much as 8ram diameter.…”
Section: Tumor Encapsulation Preventing Tumor Cell Releasementioning
confidence: 99%